AN ANALYSIS OF CODE MIXING USED ON PUELLA’S VIDEO YOUTUBE CHANNEL BY CINTA LAURA WITH NESSIE JUDGE (English Literature Study Program of Universitas Kebangsaan Republik Indonesia, 2024)
The bridge of communication used by humans is language. The phenomena of language mixture (bilingual and multilingual) is considered a language phenomenon that occurs quite often and can be recently easily found in social media content. The video content packaged in the form of Podcasts on channels owned by content creators is one of the example. The research was aim at analysing code mixing used in the conversation of video podcast broadcasted in You tube channel. The data were taken from the Puella’s You tube Channel from Cinta Laura entitled ‘Ternyata sengaja disebarkan untuk pengalihan isu | Cinta Laura Kiehl x Nessie Judge’. A descriptive qualitative method was implemented to answer the research problems formulated. The data analysis resulted shows that the celebrities involving in the podcast tent to used mainly intra-sentential code mixing for clarification some terms.